Effectiveness and Safety of a Prolonged Hemodynamic Support by the IVAC2L System in Healthy and Cardiogenic Shock Pigs - Delmas, Clément; Porterie, Jean; Jourdan, Géraldine; Lezoualc'h, Frank; Arnaud, Romain; Brun, Stéphanie; Cavalerie, Hugo; Blanc, Grégoire; Marcheix, Bertrand; Lairez, Olivier; Verwaerde, Patrick; Mialet-Perez, Jeanne (Frontiers in Cardiovascular Medicine, 2022)
Background: Mechanical circulatory supports are used in case of cardiogenic shock (CS) refractory to conventional therapy. Several technics may be used but are limited by their availability, benefit risk-ratio and/or cost. Aims: To investigate the feasibility, safety and effectiveness of a long-term support by a new available device (IVAC2L) in pigs. Methods: Experiments were carried out in male pigs, divided into a healthy (n=6) and an ischemic CS pigs (n=4) groups for a median support time of 34h and 12h, respectively. IVAC2L was implanted under fluoroscopic and TTE guidance under general anaesthesia. CS was induced by surgical ligation of LAD. An ipsilateral lower limb reperfusion was created from the Solopath® system. Reperfusion was started after 1 hour of support in healthy pigs and upon IVAC2L insertion in CS pigs. Hemodynamic and biological parameters were monitored before and on support in each group. Results: Occurrence of an ipsilateral lower limb ischemia was systematic in healthy and CS pigs in few minutes, and could be prevented or reversed by the arterial reperfusion as demonstrated by distal TcPO2 and lactate monitoring. IVAC2L support decrease pulmonary capillary wedge pressure (PCWP), increase blood pressure and cardiac output (CO) in CS pigs (15.3 +/-0.3 vs 7.5 +/-0.9 mmHg, p<0.001; 70 +/- 4.5 vs 101.3 +/- 3.1 mmHg and 4.0 +/- 0.3 vs 5.2 +/- 0.6 l/min, p < 0.001 at CS onset and after 12h of support for PCWP, SBP and CO respectively) without effect on heart rate or pulmonary artery pressure. Non-sustained ventricular arrhythmias were frequent at implantation (50%). A non-significant hemolysis was observed under support in CS pigs. Intrathoracic and at insertion site bleedings were frequent (30%). Conclusion: Long-term support by IVAC2L is feasible and associated with significant hemodynamic improvement in a porcine model. These preclinical data open the door to the study of IVAC2L in ischemic CS in humans, keeping in mind the need for systematic reperfusion of the lower limb and the associated risk of bleeding.